Dental resin monomers induce early and potent oxidative damage on human odontoblast-like cells (2021)
Resin-based dental materials consist of filler particles and different monomers that are light cured in situ to re-establish dental function and aesthetics. Due to the degree of conversion of adhesive polymers, the monomers triethyleneglycol dimethacrylate (TEGDMA) and 2-hydroxyethyl methacrylate (HEMA) are released in relatively high amounts and are susceptible to degradation, acting as bioactive compounds and affecting cell and tissues. This study aimed to assess the effect of HEMA and TEGDMA exposure on metabolic activity, membrane integrity, and cell survival of human odontoblast-like cell (hOLCs). Exposure to resin monomers for 24 h induced major changes in cell membrane integrity, metabolic activity, and survival, which were measured by the calcein method and lactate dehydrogenase release. Increased and early reactive oxygen species (ROS) production was observed leading to degradative oxidation of membrane lipids identified as malondialdehyde production. Severe alteration in mitochondria occurred due to transmembrane mitochondrial potential collapse, possibly inducing activation of apoptotic cell death. hOLCs exposure to resin monomers modified the cell redox potential, with consequences on membrane permeability and integrity, including mitochondrial function. Lipid peroxidation appears to be a key phenomenon for the membrane structures oxidation after HEMA and TEGDMA exposure, leading to cell death and cytotoxicity. hOLCs respond early by differential induction of adaptive mechanisms to maintain cell homeostasis. Modulation of oxidative stress-induced response involves the regulation of genes that encode for antioxidant proteins such as catalase and heme oxygenase-1; regulation that functions as a critical protection mechanism against oxidative cell damage induced by HEMA and TEGDMA. Ascorbic acid as an antioxidant substance mitigates the oxidative damage associated with exposure to monomers.